European experience in assessment of technical acceptability construction products - Skakun, V. (Ways to Improve Construction Efficiency, 2023)
The article examines the current state of the European system for determining the cost of works necessary for the development of documents assessing the technical acceptability of construction products. The analysis highlights significant progress in the standardization and harmonization of technical regulation methodologies across EU member states, facilitated by the Construction Products Regulation (CPR). In the EU, a reliable institutional framework for the assessment of technical acceptability has already been formed, which includes a system of regulatory and legal regulation, bodies and organizations dealing with these issues, procedures established for determining the cost of technical assessment, detailing the stages of research, testing, certification and documentation. Clear guidelines and benchmarks are developed to ensure transparency and predictability of project budgeting, including cost-benefit analysis to balance economic impact with regulatory compliance. The integration of advanced technologies, such as building information modeling (BIM) and automated testing equipment, will significantly increase the efficiency and accuracy of the system for determining the quality of construction products. These technological advances enable real-time monitoring and accurate data analysis and processing, reducing the time and cost of manual assessment. Despite these achievements, the article recognizes ongoing challenges, such as inconsistency in the implementation of the policy of technical regulation of construction products in member countries and the need for constant adaptation to technological innovations, the level of which is different in different countries. The future direction of development for the European system for determining the technical acceptability of construction products includes improving the digital infrastructure, promoting ecological construction methods and supporting small and medium-sized enterprises. Continued investment in research and development and the promotion of an innovative regulatory environment are essential to maintain the reliability, environmental focus and relevance of the decision-making system. A comprehensive review of the European system for determining the cost of work on the development of technical acceptance documents for construction products highlights significant progress in standardization, technological integration and cooperation of stakeholders, and also identifies areas for future improvement to ensure the continued efficiency and adaptability of the system in the Ukrainian construction industry.